Thyroid Cancer Incidence in Bulgaria before and after the Introduction of Universal Salt Iodization: An Analysis of the National Cancer Registry Data - Ludmila Borislavova Ivanova; Mircho Ivanov Vukov; Zdravka Gardeva Vassileva-Valerianova (Balkan Medical Journal, 2020)
Background: Thyroid cancer is the most common malignancy of the endocrine system and it has become the fastest growing cancer among women. The suspected risk factors include increased exposure to ionizing radiation during childhood, environmental pollutants, possible iodine deficiency, and excessive iodine exposure. Aims: To analyze the thyroid cancer incidence between 1980 and 2013 in Bulgaria and to determine the incidence rate before and after the introduction of universal salt iodization in 1994 in regions with different iodine deficiency levels. Study Design: Retrospective cohort. Methods: The study was a retrospective analysis of the total number of thyroid cancer cases with all histological types in Bulgaria (thyroid cancer, ICD10 code C73), diagnosed between 01/01/1980 and 31/12/2013, and retrieved from the anonymous cancer registry database of the Bulgarian National Cancer Registry. Age-standardized rates of thyroid cancer per 100,000 persons were calculated for each year of the periods mentioned below by sex and age, utilizing the WHO world reference populations with a special statistical module of the Bulgarian National Cancer Registry’s software CancerRegBG, 2011. Incidence rates were reported by age, sex, and period of diagnosis (1980-86, 1987-93, 1994-99, 2000-2006, 2007-2013). Trends among males and females were analyzed separately, as well as by age category: 0-19, 20-44, 45-64, and 65+. Annual percentage changes of age-standardized incidence rates were analyzed by Joinpoint regression to determine trends using the Joinpoint statistical software SEER* Stat Software, Version 4.1.1, 2014. Results: The age-standardized rates of thyroid cancer in Bulgaria has been increasing since 1990, being higher among women compared to men (4.68 vs 2.81). The highest age-standardized rates of thyroid cancer was observed in women in the 2007-2013 period. The only significant joinpoint was recorded in 1990 for females and in 1991 for males. The highest incidence rates was in the Smolyan district, a region with historically existing iodine deficiency and relatively high post-Chernobyl radiation exposure. Conclusion: Our results showed that, in different regions, the age-standardized thyroid cancer rates between endemic and non-endemic differ greatly depending on the radiation dose from the Chernobyl accident. The role of iodine intake in thyroid cancer remains uncertain, but iodine deficiency could be a contributing factor to the increased risk of thyroid cancer.